काष्ठमण्डपभित्र रहेका प्रतिमाहरूको विवादबारे विश्लेषणात्मक अध्ययन{An Analytical Study of the Controversy of the Images Inside the Kastamandapa} (Patan Prospective Journal, 2022)
Available with fulltext.